The Proposal and Revision of the Cell Theory - Jiahao CHEN; Xinyue LIN (Yixue yu zhexue)
This paper analyzes the historical context of the development of the cell theory and systematically examines the conditions that led to its formulation, including the need for a unified concept of plant and animal structure, the development of the concepts of organs and tissues, the introduction of the concept of the cell, and the improvement in the magnification power of experimental microscopes. These factors collectively laid the theoretical foundation for the establishment of the cell theory. The paper systematically summarizes the process of the development of the cell theory, comparing the main assertions made by Schleiden and Schwann regarding plant and animal cells. It outlines the revision process of the concepts of free cells and the theory of cell origin within the cell theory and analyzes the contributions of scholars such as Schultze, Hertwig, and Virchow to this scientific progress. A correct understanding of the significance of the cell theory is essential for the development of life sciences and biomedicine.